An additive manufacturing approach for fabrication of agarose hydrogel structures for protein sorption application - Feng Cao; Hossein Najaf Zadeh; Klaudia Świacka; Jakub Maculewicz; Dan Bowles; Tim Huber; Don Clucas (Materials & Design)
Additive manufacturing of hydrogels is a rapidly evolving field due to the unique properties of hydrogels and their potential applications in various sectors. However, the low production rate and coarse resolution of current additive manufacturing methods limit their use. This article proposes a Stencil Additive Manufacturing (SAM) method to produce agarose hydrogel structures with horizontal and vertical resolutions of 500 and 80 μm using a novel SAM printer. Compared to peer methods, the shape fidelity of printed structures was improved and errors resulting from the Barus effect were minimized to 1.7 % and 7.1 %, depending on stencil patterns. Mechanical and thermal properties of agarose hydrogels were investigated by considering chemical crosslinking and agarose concentration, and the gelation and melting temperatures were determined. The analysis of hydrogel microstructures illustrated the change in porosity by regulating agarose concentration and the gelation rate. Static bovine serum albumin binding tests were performed using printed structures with varying concentrations and resolutions to explore the protein adsorption capacity. The results indicated that structure resolutions affect the adsorption capacity dramatically, which was increased from 100.44 to 144.13 mg/ml as resolutions were improved from 500 to 350 µm. Therefore, SAM-printing agarose hydrogels with periodic structures demonstrates potential in applications.